الرشوة آثارھا كما یعرضھا القران دراسة موضوعیة - بوته, أم الخير (University of Eloued جامعة الوادي, 2017)
هدفت الدراسة إلى موضوع الرشوة دراسة موضوعية إذ أن الرشوة من الأمور المنكرة التي ابتليت ا مجتمعات المسلمين وهي مرض عضال وداء خطير ،يفسد ا تمعات ويضيع الحقوق وقد تعرض لها القران في عدد من الآيات فهي ضرب من ضروب أكل أمول الناس بالباطل فهي ماحقة للبركة ومزيلة لها تعد من كبائر الذنوب التي حرمها الله على عباده بقوله ولعن رسوله صلى الله عليه وسلم من فعلها بدليل حديثه "لعن رسول الله الراشي والمرتشي فالواجب اجتنا ا والحذر منها وتحذير الناس من تعاطيها لما فيها من الفساد العظيم والإثم الكبير والعواقب الوخيمة وهي من الإثم والعدوان وقول رسول الله صلى الله عليه وسلم:"كل لحم نبت من سحت فالنار أولى به". ولعلاجها لابد من بث الوعي بخطرها وضررها وتشجيع الناس على البدائل المشروعة،ولابد من غرس عقيدة الإيمان بالله وما يترتب عنها من سلوك قويم. The study aimed at the subject of bribery is an objective study since bribery is an evil thing that has plagued Muslim communities are a severe disease and a serious disease, spoil the communities and lose the rights have been exposed to them The Qur'an in a number of verses is a kind of eating people's misfortunes by vanity, which is a blessing to the blessing and a substitute for it It is one of the major sins that Allaah has forbidden to His slaves by saying And cursed the Messenger of Allah peace be upon him from doing the evidence of his speech, "cursed the Messenger of Allah Rashi and Marthi duty And warning of the people of abuse of the great corruption and great sin and the terrible consequences It is sin and aggression And the Messenger of Allaah (peace and blessings of Allaah be upon him) said: "All flesh is sprouted from the sun, and the fire is better than it." And to treat them must be aware of the danger and damage and encourage people to legitimate alternatives, and must be instilled The doctrine of faith in God and the consequent behavior is correct
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: الرشوة – الجريمة – الفساد المالي - الجنايات; Bribery - Crime - Financial corruption - Crimes